2022
DOI: 10.5688/ajpe8688
|View full text |Cite
|
Sign up to set email alerts
|

Instruction and Simulation to Improve Pharmacy Students’ Knowledge and Confidence Regarding Assessment of Penicillin Allergies

Abstract: Objective. To evaluate pharmacy students' knowledge and confidence regarding penicillin allergy assessment and skin testing (PAAST) before and after a focused didactic instruction and simulation (FDIS). Methods. A multicenter, quasi-experimental, cross-sectional survey study was performed among pharmacy students before and after FDIS on PAAST at two schools of pharmacy. The FDIS on PAAST consisted of an infectious disease faculty-led seminar, student-led penicillin allergy counseling interviews, penicillin ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, students generally enjoyed this COVID‐19 IDC and found it useful to their practice as a future pharmacist. This study's findings were consistent with those observed in a similar active learning, didactic instruction approach of penicillin allergy management, where pharmacy students' knowledge and confidence improved following this instructional method 18 . Based on these findings and overall positive impressions from the students, the ID pharmacist faculty continue to deliver the IDC in the same semester and format.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, students generally enjoyed this COVID‐19 IDC and found it useful to their practice as a future pharmacist. This study's findings were consistent with those observed in a similar active learning, didactic instruction approach of penicillin allergy management, where pharmacy students' knowledge and confidence improved following this instructional method 18 . Based on these findings and overall positive impressions from the students, the ID pharmacist faculty continue to deliver the IDC in the same semester and format.…”
Section: Discussionsupporting
confidence: 85%
“…This study's findings were consistent with those observed in a similar active learning, didactic instruction approach of penicillin allergy management, where pharmacy students' knowledge and confidence improved following this instructional method. 18 Based on these findings and overall positive impressions from the students, the ID pharmacist faculty continue to deliver the IDC in the same semester and format. However, the IDC is delivered in the classroom and utilizes the updated COVID‐19 therapeutics and guidance from the NIH and IDSA guidelines.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations